Analysis of Resistor Color Differences Against Resistance Values - Mahendra Abiyaksa; Muhamad Khoirul Anam; Ratna Mustika Yasi (Journal of Educational Engineering and Environment, 2022)
A resistor is an electronic component that functions as an electric current inhibitor which has units of ohms and has different values based on the difference in the position of the color of the bracelet on the resistor in the experiment, the value of 330 from orange, orange, brown, gold, 1000 from brown, black, red, gold and 130Ω of brown, red, brown, gold, and 100Ω of brown, black, brown, gold. The resistor value also has a difference when it is determined using a calculation based on a formula with a calculation using a multimeter measuring instrument, it is influenced by the tolerance value on the resistor where the color is orange, orange, brown, gold with a gold color with a tolerance value of 5%, the value is 330Ω with calculations based on the formula and obtained 313 by calculation using a multimeter measuring instrument, brown, red, brown, gold, with a gold color with a tolerance value of 5% obtained a value of 1000 by calculations based on the formula and obtained 942 by calculations using a multimeter measuring instrument, brown, black, red, gold , with a gold color with a tolerance value of 5% obtained a value of 130 by calculation based on the formula and obtained 122 by calculations using a multimeter, brown, black, brown, gold, gold color with a tolerance value of 5% obtained a value of 100 with calculations based on the formula and obtained 94Ω by calculation using the tool measure multimeter.